Perceptions of victim and offender culpability in non-consensual distribution of intimate images - Zvi, Liza (Psychology, crime & law, 2021)
This research focused on expanding the limited empirical literature related to perceptions of non-consensual distribution of private sexual images by examining whether the source of the distributed images affects judgments and blame attributions of both victims and offenders. We devised a scenario with male offenders and female victims while manipulating the way in which the misappropriated intimate images were taken (self-taken by the victim vs. stealth-taken). In both conditions and irrespective of the victim's blame, the offender was perceived as highly blameworthy and deserving to be tried and severely punished. Even so, victim-blaming was evident toward a victim whose images were self-taken, and feelings toward the victim affected perceptions of deserved punishment for the offender. Gender differences showed that men significantly blamed the victim more than women and suggested that women's fear of becoming a victim of NCII was greater than men's. The findings support the notion that NCII is no different than other forms of sexual abuse, where female victim-blaming, especially by males, is an established fact.